Hubungan antara Self-Compassion dan Dukungan Sosial Teman Sebaya dengan Prokrastinasi Akademik Mahasiswa UKM - Rizqiyah, Divany Maulida; Ahyani, Latifah Nur (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the relationship between self-compassion and peer social support with academic procrastination of UKM students. Respondents in this study were undergraduate students who participated in UKM as many as 110 respondents from 15 UKM. The sampling technique used was non-probability sampling with quota sampling type. This research instrument used a scale of self-compassion, peer social support, and academic procrastination. The results of the correlation coefficient of the three variables were 0.341 with a p value of 0.000 (p <0.01) and the proposed hypothesis was accepted with an effective contribution of 11.6%, meaning that there is a very significant negative relationship between self-compassion and peer social support with academic procrastination. The results of the study showed that self-compassion and peer social support can affect academic procrastination of UKM students. The results of this study are expected to provide information to UKM students about the importance of being kind, compassionate, and understanding towards themselves and how supportive peer social support plays a role, especially when facing difficulties or failures.